Extra- cellular Pectinase Activity of Post-harvest Fungi from Papaya Fruits in Presence of Different Influencing Factors - Ashok M. Chavan2, G.M. Rathod1* and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The present paper deals with the study of pectinase enzyme activity of post-harvest fungi of papaya fruits under the influence of nutritional factors, antibiotics, vitamins and fungicides. It was found that carboxy methyl cellulose (CMC), sodium sulphate; ferrous sulphate, barium chloride, sodium chloride, magnesium chloride, zinc, ferrous, manganese, copper, barium, fungicides and ampicillin inhibits the pectinase action of all tested post-harvest fungi while other factors induces the same.Â  -------------------------------------------------------------------------------------------------------- 1Dept. of Botany, Shrikrishna Mahavidyalaya, Gunjoti, Dist Osmanabad, Aurangabad; 2Seed pathology and Fungal Biotechnology Laboratory, Dept. of Botany, Dr. Babasaheb Ambedkar Marathwada University, Aurangabad- 431 004. (M.S.) India. * Corresponding Author, Email: skmg_gulabrathod@rediffmail.com Please Cite This Article As: G.M. Rathod and Ashok M. Chavan. 2010. Extra- cellular Pectinase Activity of Post-harvest Fungi from Papaya Fruits in Presence of Different Influencing Factors. J. Exp. Sci. 1(2): 07-11.